Plan de marketing digital en redes sociales para el posicionamiento del gimnasio Reino Fitness. - Costales Tapia, Leslie Gabriela (2024)
Digital marketing refers to promoting and advertising companies that offer products or services through online media, reaching a larger audience. These digital media help position the Company by disseminating interesting content for the user. The purpose of this project is to increase the visibility of the service and products offered at the Reino Fitness Gym with the creation of a digital marketing plan on social networks. This involves creating informative and visually attractive content for the user, with the aim of promoting the growth of the gym by encouraging future customers to join. A qualitative approach was used in the research, where observation sheets were made from the leading social networks, where different particularities were observed to determine the lack obtained; it also used a quantitative approach, where information was collected from clients and non-clients of the gym. Through these statistical data, we collect information on which social network is the most used by clients. Through the mixed approach, more detailed information is collected to create the target, the SWOT analysis, the Buyer persona, and the Company organization chart, facilitating the elaboration of graphic pieces. The results indicate that the main social networks used are Instagram, Facebook, and TikTok, so graphic pieces will be created mainly on these social networks. As a result of the research, a brand was created with its corporate identity manual, digital graphicpieces, and audiovisuals for its social networks.